2022
DOI: 10.1111/1365-2435.14199
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific and intraspecific variation of tree branch, leaf and stomatal traits in relation to topography in an aseasonal Amazon forest

Abstract: Tropical forest responses to variation in water availability, which are critical for understanding and predicting the effects of climate change, depend on trait variation among trees. We quantified interspecific and intraspecific variation in 18 branch, leaf and stomatal traits for 19–72 dominant tree species along a local topographic gradient in an aseasonal Amazon terra firme forest, and tested trait relationships with tree size, elevation, and species' topographic associations. We further tested whether cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 74 publications
0
8
1
Order By: Relevance
“…This suggests that the plants in this system may have developed different independent mechanisms of tolerating and avoiding drought stress. This is contrary to previous studies in other systems that found coordination among the stomatal, hydraulic, and leaf traits associated with drought tolerance [ 60 , 71 , 72 ]. Additional research is required to understand the interactions and tradeoffs in the different drought tolerances and avoidance mechanisms employed by tropical montane plant species and the implications of these mechanisms for plant performance, as well as the potential effects of other abiotic and biotic factors (e.g., edaphic factors and competition, respectively).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This suggests that the plants in this system may have developed different independent mechanisms of tolerating and avoiding drought stress. This is contrary to previous studies in other systems that found coordination among the stomatal, hydraulic, and leaf traits associated with drought tolerance [ 60 , 71 , 72 ]. Additional research is required to understand the interactions and tradeoffs in the different drought tolerances and avoidance mechanisms employed by tropical montane plant species and the implications of these mechanisms for plant performance, as well as the potential effects of other abiotic and biotic factors (e.g., edaphic factors and competition, respectively).…”
Section: Discussioncontrasting
confidence: 99%
“…Twelve hours after boiling, we took a second conductivity measurement (C 2 ). We calculated the relative solute leakage (%) as (C 1 − C 0 )/(C 2 − C 0 ) × 100 [ 59 , 60 ]. Higher SL values indicate greater cytorrhysis when exposed to desiccating conditions and thus a lower relative leaf drought tolerance.…”
Section: Methodsmentioning
confidence: 99%
“…We note, however, that our study does not capture the full range of rainfall regimes of South America, but evidence from other sites seem to align with our hypotheses and results. In a high MAP, aseasonal forest in Northwestern Amazônia, no differences were found between hills and valleys for several branchand stomata-level traits [94], although P 50 directly was not measured. Where seasonal water stress is minimal, the relative importance of a shallow WT for drought resistance is likely small, blurring the topographic signal.…”
Section: Discussionmentioning
confidence: 80%
“…This suggests that the resource use traits studied here mostly reflect species’ edaphic optima and not their range of resource use. It is also worth noting that intraspecific trait variation may have partly limited the detection of niche‐trait association at the species level (Zuleta et al, 2022), but we lack enough trait measurements across habitats for each species to have more accurate insights.…”
Section: Discussionmentioning
confidence: 99%